Pituitary adenoma apoplexy for ischemic infarction: three cases report and literature review - ZHAO Peng⁃fei; WANG Jia⁃liang; WANG Yan; SUN Cheng⁃yuan; LIU Hai⁃peng (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To explore the pathogenesis, clinical manifestations, imaging and endocrine function characteristics, treatment methods, pathological characteristics and prognosis of pituitary adenoma apoplexy for ischemic infarction. Methods and Results All 3 patients with pituitary adenoma apoplexy for ischemic infarction who were hospitalized in Affiliated Hospital of Hebei University from January 2021 to April 2022 were selected. All 3 patients presented with clinical manifestations such as headache, vision loss, cranial nerve palsy, and endocrine abnormalities. Preoperative endocrine examination indicated that one patient had decreased cortisol and prolactin levels. Preoperative MRI showed that all were large adenomas invading the cavernous sinus, hyperintensity on T1WI and T2WI, and uneven ring enhancement of the tumors. All 3 patients underwent endoscopic transsphenoidal resection of pituitary adenoma. Postoperative pathology confirmed pituitary adenoma with necrosis, all of which were coagulative necrosis. All 3 patients were finally diagnosed with pituitary adenoma apoplexy for ischemic infarction. Postoperatively, the clinical symptoms of all 3 patients improved significantly; one patient developed hypothyroidism and was treated with hormone supplementation. Conclusions The clinical features of pituitary adenoma apoplexy for ischemic infarction are relatively typical. Multidisciplinary cooperation should be carried out, and the best treatment plan should be formulated based on the clinical characteristics of the patients.